TECHNICAL AND ECONOMIC ANALYSIS OF A PLANT SCALE GREEN HOUSE DRYER FOR RED ONION BULB - Nurhasanah, Ana; *, Suparlan; S, Suherman; Mokhtar, Saleh (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
A green house dryer for red onion bulb with capacity 1000 kg/batch was designed and tested. Dry wood was used as primary energy source of furnace for heating drying air, in which the drying room is also heated by solar energy. The ambient temperature and humidity of air are 28.9 0C and 70.4%, respectively. The velocity and temperature of drying air are 5.1 m/s and 54.20C, respectively. The result show 1000 kg of red onion bulb with initial moisture content (wb) 0.87 for leaf and 0.86 for bulb can be dried become 0.14 and 0.82 in 35 hours. The temperature profile and moisture content of bulb in dryer room are almost homogeneous. After 1 month storage, yield and bulb damage are 77.2% and 1.68%, respectively, is higher comparing by solar dryer in which yield is 72%. Economic analysis as B/C ratio give 4.6.